Development of STEP-NC based machining system for machining process information flow - Kassim, Noordiana; Yusof, Yusri; Mohamad, Mahmod Abd Hakim; Janon, Mohd Najib; Mohd Hanifa, Rafizah (Trans Tech Publications, 2013)
To realize the STEP-NC based machining system, it is necessary to perform machining feature extraction, generating machine-specific information, and creating a relationship between STEP-NC entities. A process planning system of a STEP-NC information flow that starts with constructing a machining feature from a CAD model will be developed. In this paper, a further indepth study of the implementation and adaptation of STEP-NC in manufacturing is studied. This study will help to understand how the data from CAD/CAM can be converted into STEP-NC codes and the machining process will be based on the STEP-NC codes generated.